The additional yield of a periodic screening programme for open-angle glaucoma: a population-based comparison of incident glaucoma cases detected in regular ophthalmic care with cases detected during screening. Issue 9 (22nd August 2008) - Stoutenbeek, R; de Voogd, S; Wolfs, R C W; Hofman, A; de Jong, P T V M; Jansonius, N M
Abstract : Aim: To study the additional yield of a periodic screening programme for open-angle glaucoma (OAG) by comparing, in a population-based setting, incident OAG (iOAG) cases detected in regular ophthalmic care with those detected during screening. Methods: Participants aged 55 and over from the population-based Rotterdam Study underwent the same ophthalmic examination at baseline (1991–3) and follow-up (1997–9), including visual field testing and simultaneous stereo optic disc photography. Of 3842 participants, 87 (2.3%) developed iOAG during a mean follow-up time of 6.5 years. Of these 87 iOAG cases, 78 (90%) were included in this study. Results: Of the 78 iOAG cases detected at follow-up, 23 (29%) had already been detected before during regular ophthalmic care. The remaining 55 (71%) undetected iOAG cases more often showed glaucomatous optic neuropathy without glaucomatous visual field loss (29 of 55 (53%)) as compared with the detected cases (four of 23 (17%); p = 0.009). Of the undetected iOAG cases, only four had developed significant visual field loss in their better eye. Conclusion: The additional yield of a periodic OAG screening programme is lower than expected from published prevalence data. In the discussion, the authors estimate that—in a white population with a low prevalence of pseudoexfoliation—about one in 1000 screened persons could be saved from bilateral end-stage OAG.